The Relationship of Academic Educational Status with Job Stress and Occupational Burnout among Nurses and Paramedicine Practitioners in Hospitals Affiliated with the Qom University of Medical Sciences in 2017 - Meysam Hosseini Amiri; Hossein Mirzai (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Evidences showed that some nursing and paramedicine students reported difficulties in their education and work places. This study aimed to investigate the relationship of academic education status with job stress and occupational burnout among the nurses and paramedicine practitioners in the hospitals affiliated with Qom University of medical sciences. Methods: A descriptive-analytical study was conducted on 187 individuals selected by the random convenience sampling method. The demographic, Maslach Burnout, as well as Health and Safety Executive stress questionnaires were used in present study. Descriptive statistics and Pearson correlation coefficient test, Chi-square test, ANOVA test, and independent t-test were applied for data analysis, using the SPSS version 22.0. Results: Of the total participants, 56.6 percent were students, whereas the other 43.4 percent were not students. The findings showed that 82 student staffs (77.4%) and 59 non-student staffs (72.8%) had high levels of stress. A significant correlation was found between the level of stress and individuals' burnout (r = -0.323, P ˂ 0.05). A significant difference was observed between the student and non-student staffs with regard to emotional exhaustion (18.50 ± 10.83 versus 23.55 ± 11.16; P = 0.002) and personal accomplishment (28.75 ± 6.83 versus 25.69 ± 5.13; P = 0.001). Conclusion: According to the results, paramedical staffs and nurses work in stressful work places. Furthermore, due to the role of education in enhancing motivation, education can be considered as an important factor to improve emotional exhaustion.